The Influence of Work Environment and Work-Life Balance on Teacher Performance with Motivation as a Mediator - Soepardi, Johannes; Lianto, Lianto; Ginting, Sunardi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to analyze the mediating role of work motivation in the influence of the work environment and work-life balance on the performance of teachers and employees. The research was conducted at SMK Santa Monika Sungai Raya using a quantitative approach and survey method. Data were collected through questionnaires distributed to teachers and employees and then analyzed using WarpPLS-based Structural Equation Modeling (SEM). The research results show that the work environment and work-life balance have a positive and significant effect on motivation, with path coefficients of 0.493 (p = 0.001) and 0.501 (p < 0.001), respectively. The work environment also has a significant effect on performance (β = 0.438; p = 0.004). This research also indicates a weak significance for the mediating role of the motivation variable (β = 0.229; p = 0.092). In this mediation model, it was found that work-life balance does not have a direct effect on performance (β = 0.183; p = 0.148).